Contributions of the Hippocampus and Medial Prefrontal Cortex to Energy and Body Weight Regulation - Davidson, T. L. (2009)
The effects of selective ibotenate lesions of the complete hippocampus (CHip), the hippocampal ventral pole (VP), or the medial prefrontal cortex (mPFC) in male rats were assessed on several measures related to energy regulation (i.e., body weight gain, food intake, body adiposity, metabolic activity general behavioral activity, conditioned appetitive responding). The testing conditions were designed to minimize the nonspecific debilitating effects of these surgeries on intake and body weight. Rats with CHip and VP lesions exhibited significantly greater weight gain and food intake compared to controls. Furthermore, CHip-lesioned rats, but not rats with VP lesions, showed elevated metabolic activity, general activity in the dark phase of the light-dark cycle, and greater conditioned appetitive behavior, compared to control rats without these brain lesions. In contrast, rats with mPFC lesions were not different from controls on any of these measures. These results indicate that hippocampal damage interferes with energy and body weight regulation, perhaps by disrupting higher-order learning and memory processes that contribute to the control of appetitive and consummatory behavior.